2005
DOI: 10.1093/ndt/gfh916
|View full text |Cite
|
Sign up to set email alerts
|

Sodium retention in rats with liver cirrhosis is associated with increased renal abundance of NaCl cotransporter (NCC)

Abstract: Enhanced abundance of NCC was observed in the initial stage after BDL, followed by a marked decrease. ENaC transcription, translation or cell surface abundance was not increased after BDL.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…33 Along with the uncertainties concerning the role aldosterone and MR, there is no consensus either on the renal site of sodium retention. Although several reports in experimental models of cirrhosis show that sodium retention originates along the aldosterone-sensitive nephron segments, 29,32,[34][35][36][37][38][39] other reports concluded to the thick ascending limb of Henle's loop as the main site of sodium retention in rat models. 40,41 The present study aimed at (1) localizing the site of sodium retention along the nephron, and (2) at determining the role of aldosterone and MR in sodium retention.…”
mentioning
confidence: 96%
“…33 Along with the uncertainties concerning the role aldosterone and MR, there is no consensus either on the renal site of sodium retention. Although several reports in experimental models of cirrhosis show that sodium retention originates along the aldosterone-sensitive nephron segments, 29,32,[34][35][36][37][38][39] other reports concluded to the thick ascending limb of Henle's loop as the main site of sodium retention in rat models. 40,41 The present study aimed at (1) localizing the site of sodium retention along the nephron, and (2) at determining the role of aldosterone and MR in sodium retention.…”
mentioning
confidence: 96%
“…Loss-of-function mutations of NCC (Gitelman syndrome) cause renal salt wasting with hypotension, hypokalemic alkalosis, and hypocalciuria, 3 whereas increased NCC activity because of mutations within the NCC-regulating with-no-lysine kinase 1 (WNK1) or WNK4 (familial hyperkalemic hypertension) are associated with severe salt-sensitive hypertension, hyperkalemia, metabolic acidosis, and hypercalciuria. 4 Increased NCC expression has been linked to renal Na + retention in liver cirrhosis, 5 diabetes mellitus, 6 b-adrenergic stimulation, 7 and immunosuppressive treatment. 8 The clinical significance of the DCT is also emphasized by clinical trials that confirmed the DCT as an important target for antihypertensive therapy.…”
mentioning
confidence: 99%
“…This is probably best explained by the complex regulation of ENaC, the methodological difficulties linked with the assessment of the kinetics of the 3 constituents (alpha, beta, gamma) of this channel, and the apparent biphasic changes of ENaC abundance as a function of time during the induction of cirrhosis. 34,[36][37][38] Besides ENaC, there is the thiazide-sensitive NaCl cotransporter, which is a second aldosterone-dependent transporter and thus presumably a 11␤-HSD2-dependent transporter in the distal tubule. 39 Whether this transporter is increased or decreased in cirrhotic rats is a matter of debate.…”
Section: Biology Of 11␤-hsd2mentioning
confidence: 99%
“…39 Whether this transporter is increased or decreased in cirrhotic rats is a matter of debate. 37,38,40,41 Renal sodium retention appears in at least some models before ascites is produced. [2][3][4] Thus, a cross-talk between liver and kidney has to occur early in the cirrhotic disease state.…”
Section: Biology Of 11␤-hsd2mentioning
confidence: 99%